2017
DOI: 10.18203/2320-6012.ijrms20172573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the epidemiology and needs of oral cancer patients from Aurangabad district, Maharashtra, India

Abstract: Background: India is facing burden of non-communicable diseases and oral cancer is one of the leading public health issue. This is a descriptive study from Aurangabad district, Maharashtra, India to evaluate epidemiologic profile of oral cancer patients who underwent treatment during 2012 to 2016.Methods: Demographic and clinical profile of 500 patients was recorded with validated questionnaire.Results: With male: female ratio was 2.90:1; the mean age of the patients of oral cancer was 47.73 years. Tobacco con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…From various epidemiological studies, it has been shown that tobacco (smokeless or smokeable) is the main cause of oral cancer incidences worldwide [144–150]. Tobacco contains carcinogens, radioactive elements, and heavy‐metal ions capable of inducing cellular damage and genetic mutations in the oral mucosa [151–157].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From various epidemiological studies, it has been shown that tobacco (smokeless or smokeable) is the main cause of oral cancer incidences worldwide [144–150]. Tobacco contains carcinogens, radioactive elements, and heavy‐metal ions capable of inducing cellular damage and genetic mutations in the oral mucosa [151–157].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SSFA2 isoforms are potentially suitable for interactions with a diverse array of molecular partners (proteins, RNA, and/or DNA) and regulating multiple molecular pathways [142]. The TDSs of SSFA2 isoforms designed using RaptorX were validated From various epidemiological studies, it has been shown that tobacco (smokeless or smokeable) is the main cause of oral cancer incidences worldwide [144][145][146][147][148][149][150]. Tobacco contains carcinogens, radioactive elements, and heavy-metal ions capable of inducing cellular damage and genetic mutations in the oral mucosa [151][152][153][154][155][156][157].…”
Section: Notementioning
confidence: 99%
“…Carcinoma of oral tongue is the most common oral cancer in the world with a reported incidence of 17.8-52% and the second commonest cancer of oral cavity in India 1 . Tongue, because of its structure and function is prone for early local and regional spread of cancer.…”
Section: Introductionmentioning
confidence: 99%